State, society, and land in Jordan - Fischbach, Michael R. (Leiden ; Boston : Brill, 2000)
Examines how state and society conceptualized land ownership in Jordan from the late Ottoman era through the 1950s, and how the resulting interaction between them shaped the socio-economic and political contours of modern Jordan.
Acknowledgments; Note on Transliteration; Abbreviations; List of Tables; Introduction; Chapter One: Ottoman and Local Conceptualizations of Land; Chapter Two: Land in the Wake of Ottoman Policies; Chapter Three: Land in the Early Years of the Emirate; Chapter Four: The British Land Program; Chapter Five: Results of the Land Program; Chapter Six: Land Policy, Socio-Economic Structures, and Politics; Chapter Seven: Land and the Conceptualization of Jordan; Conclusion; Bibliography; Index; Illustrations.
Includes bibliographical references (pages 213-225) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Land tenure -- Jordan -- History -- 19th century; Land tenure -- Jordan -- History -- 20th century; Land use -- Jordan -- History -- 19th century; Land use -- Jordan -- History -- 20th century; Land value taxation -- History -- 19th century; Land value taxation -- History -- 20th century; Utilisation du sol -- Jordanie -- Histoire -- 19e siècle.; Utilisation du sol -- Jordanie -- Histoire -- 20e siècle.; Propriété foncière -- Impôts -- Histoire -- 19e siècle.; Propriété foncière -- Impôts -- Histoire -- 20e siècle.; BUSINESS & ECONOMICS -- Real Estate -- General; Land tenure; Land use; Land value taxation; Jordan; Grundeigentum; Sozioökonomischer Wandel; Jordanien; Grondpolitiek; Grondbezit; 1800-1999; History